2019
DOI: 10.1186/s40425-019-0810-y
|View full text |Cite
|
Sign up to set email alerts
|

Soluble immune checkpoint-related proteins as predictors of tumor recurrence, survival, and T cell phenotypes in clear cell renal cell carcinoma patients

Abstract: BackgroundImmune checkpoint inhibitors have achieved unprecedented success in cancer immunotherapy. With the exception of a few candidate biomarkers, the prognostic role of soluble immune checkpoint-related proteins in clear cell renal cell cancer (ccRCC) patients is largely uninvestigated.MethodsWe profiled the circulating levels of 14 immune checkpoint-related proteins panel (BTLA, GITR, HVEM, IDO, LAG-3, PD-1, PD-L1, PD-L2, Tim-3, CD28, CD80, CD137, CD27 and CTLA-4) and their associations with the risk of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 36 publications
5
127
0
2
Order By: Relevance
“…Elsewhere, CD40 and HVEM messenger RNAs were coexpressed in the bioinformatic analysis of bladder cancer in the Cancer Genome Atlas database [47]. HVEM is a ligand of B-and T-lymphocyte attenuator (BTLA) and soluble BTLA in combination with sTIM-3 may be able to predict the rates of disease recurrence and survival among renal cell cancer patients [48].…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, CD40 and HVEM messenger RNAs were coexpressed in the bioinformatic analysis of bladder cancer in the Cancer Genome Atlas database [47]. HVEM is a ligand of B-and T-lymphocyte attenuator (BTLA) and soluble BTLA in combination with sTIM-3 may be able to predict the rates of disease recurrence and survival among renal cell cancer patients [48].…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, soluble LAG3, which is known to function as a dendritic cell activator, was also recently shown to be associated with advanced KIRC stage. 40 Tumor-specific LAG3 upregulation might be an immune evasion phenotype similarly to PD-L1 upregulation or upregulation of other immune checkpoints. This hypothesis needs further functional evaluation.…”
Section: Open Accessmentioning
confidence: 99%
“…Moreover, PD-L1 is also expressed in non-immune cells, such as cornea cells, vascular endothelial cells, mesenchymal stem cells, and keratinocytes, and it is often inducibly or constitutively upregulated on tumor cells of lots of solid and hematologic tumors (20). Interestingly, PD-L1 has been found in a soluble form (sPD-L1) in the patients' serum with tumors, such as melanoma and lung adenocarcinoma (22)(23)(24)(25). Theodoraki et al also demonstrated that sPD-L1 was found in plasma of patients with HNSCC (26).…”
Section: Expression Features Of Pd-l1 and Pd-1 In Hnsccmentioning
confidence: 99%